Mecanismos de defesa da soja [Glycine max (L.) Merril] em diferentes fases de desenvolvimento contra o fungo Cercospora kikuchii e caracterização da toxicidade in vitro da SBTX como fungicida - Arantes, Mariana Reis (2020)
Soy emerges as one of the main monocultures that drives Brazilian economy. Thus, several strategies are used to reduce the losses that plague this commodity from planting to harvest. Fungi are the main pathogens that cause diseases in plants and several species are routinely studied to create methods and products that will reduce and eradicate the damage caused by these diseases. The necrotrophic fungus Cercospora kikuchii affects aerial parts of soy at the end of the cycle, causing Cercospora leaf blight and purple seed stain and the symptoms usually appear in the later stages of plant growth at the beginning of grain set and can culminate in early defoliation of the upper leaves. The soybean toxin (SBTX) was isolated from soybean seeds and displays antifungal activity against filamentous fungi of agronomic interest and its mechanism of action was elucidated by pathogenic yeasts to man. Although SBTX presents potential to promote or increase the resistance of cultivating soy to fungal diseases, information on its safety of use for man is scarce. Therefore, this work aimed to compare the defense response of soybean in the young and adult phase when inoculated with C. kikuchiii and to investigate the effects of SBTX on non-target cells to ensure its safety of use as an antifungal compound. The presence of the fungus was confirmed in both stages of soybean development, however, only in the adult leaves the symptoms were visualized, the production of cercosporin by the fungus detected and the enhance of CFP expression (Cercosporin Facilitator Protein). Young plants exhibited an increase in the enzymatic activity of superoxide dismutase, as well as more pronounced increases in peroxidase and catalase, resulting in a microenvironment with low production of H2O2. In addition, young plants were still able to enhance PR proteins synthesis earlier when compared to adult plants. Regarding the safety of use of SBTX assessment, it was not able to inhibit the growth of bacteria Salmonella enterica, Bacillus subtilis and Staphylococcus aureus. Furthermore, SBTX did not affect the viability of erythrocytes, neutrophils and Caco-2 cells. However, it altered the gene expression profile of Caco-2 cells after 24 h of exposure, with an upregulation of genes involved in the cell cycle pathway and immune system responses, whereas the genes involved in cholesterol synthesis were downregulated. Thus, despite SBTX did not exhibit negative effects for bacteria or cytotoxicity in mammalian cells, it altered gene expression of some metabolic pathways of Caco-2 cells, indicating that further analysis should be conducted to warrant the safe use of this protein.